The Covariance Matrix of the Limited Information Estimator and the Identification Test: Comment - Fisher, Franklin M.; Kadane, Joseph B. (Econometrica, 1972)
IN THEIR ARTICLE [5], Liu and Breen propose a new estimator of the large-sample asymptotic covariance matrix for the limited information maximum likelihood estimator in simultaneous equations, and express surprise that their estimator is different from the estimator proposed by Chernoff and Divinsky [1]. Additionally, they question the interpretation of a statistic used in the past to test over-identifying restrictions.